2009
DOI: 10.1016/j.bbr.2009.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Female fear: Influence of estrus cycle on behavioral response and neuronal activation

Abstract: Our observation that male rats innate fear response differed with hormonal status, as well as the higher prevalence of fear and anxiety disorders in human females led to the current investigation of the impact of phases of the estrous cycle on innate fear responding. Female rats in different phases of the cycle were exposed to an innate fear-inducing stimulus (2,5-dihydro- 2,4,5-trimethylthiazoline, TMT odor) and monitored for changes in behavior and brain activation. Behavioral data showed freezing responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 53 publications
4
26
1
Order By: Relevance
“…Most of the areas were cortical and regions such as the BNST, amygdala, septum and prefrontal cortex did not distinguish between BA and TMT. This differs somewhat from Chen et al (2009), which measured the BOLD signal response to TMT in female rats and reported increased in BOLD in BNST, septum, hypothalamic nuclei, hippocampus, in addition to similar regions reported in the present study and in Febo and Pira (2011). However, Chen et al (2009) did not include a control odor during scanning which makes it difficult to compare the studies and to discern whether the pattern of BOLD signal changes corresponds to innate fear circuitry or the neural response to an aversive odor.…”
Section: Discussioncontrasting
confidence: 86%
“…Most of the areas were cortical and regions such as the BNST, amygdala, septum and prefrontal cortex did not distinguish between BA and TMT. This differs somewhat from Chen et al (2009), which measured the BOLD signal response to TMT in female rats and reported increased in BOLD in BNST, septum, hypothalamic nuclei, hippocampus, in addition to similar regions reported in the present study and in Febo and Pira (2011). However, Chen et al (2009) did not include a control odor during scanning which makes it difficult to compare the studies and to discern whether the pattern of BOLD signal changes corresponds to innate fear circuitry or the neural response to an aversive odor.…”
Section: Discussioncontrasting
confidence: 86%
“…Cycle status affects anxiety [1], fear [6], and aversion in rodents [7]. Rats in receptive phases of their cycle are less anxious, spending more time in open arms of elevated plus maze and in brightly lit areas, showing decreased latency in leaving dark chambers, decreased freezing after a foot shock, and increased interaction with conspecifics, as compared to animals in diestrus.…”
Section: Discussionmentioning
confidence: 99%
“…One scientist may conclude that the trait ''is innate'' and the other that it is not, as we saw in the cowbird case. Another puzzling situation is when scientists are investigating the causes of a trait that has already been claimed to be ''innate,'' such as ''innate fear,'' which, though it does not require prior exposure to the source of fear, is nonetheless influenced by other causes worth studying, such as neonatal maternal separation or phase in the estrus cycle (Stevenson et al 2009;Chen et al 2009). Similarly, cuttlefish have been claimed to have an ''innate preference'' for shrimp because they will choose shrimp over crab at their first feeding, never having eaten either before.…”
Section: Avoiding Confusion About Innatenessmentioning
confidence: 99%